Improve Product Sustainability Through DFE Approach On Design Of Home Appliances : A Case Study On Electric Iron - Wong , Nelson Wye Leong (UTeM, 2010)
The development of electronic equipment and sustainability are a recent combination of conditions that come from the recognition of the importance of design, production, and material selection, kind of product, use and final disposal which are having impact on the environment. These urge manufacturers to consider environmental aspects at all stages of the product development process and increase resources efficiency at all phases of product life cycle. This report demonstrates the application of Design for Environment (DFE) concept to develop a sustainable product. The objectives are to integrate Design for Environment (DFE) tools into product design and development process; to carry out Sustainability analysis on product design to reduce environment load; and to carry out Life Cycle Assessment (LCA) study and compare the environmental performance of the new product with the benchmark product using the SimaPro software. The methodology carried out in this report is by developing an existing product as a benchmark and implementing DFE tools and guidelines to design a new sustainable product. Based on the evaluation of available benchmark product and analysis of the product, a new sustainable redesign product was developed accordingly to environment variables. Finally, the evaluation and comparison of environment impact and human health of the existing product and sustainable redesign product is carried out with the life cycle assessment (LCA) method. The environment impact is analyzed by mean of SimaPro software which is one of the LCA widely used software. After thoroughly analyses on environmental impact and detailed evaluation of the benchmark product performance, a new sustainable product is redesigned or improved in a way of environmental perspective. The sustainable product is expected to cause the lowest environmental impact throughout its life cycle.